Intact transferrin and total plasma glycoprofiling for diagnosis and therapy monitoring in phosphoglucomutase-I deficiency - Abu Bakar, Nurulamin; Thiel, Christian (Translational research, 2018)
Phosphoglucomutase 1 (PGM1) deficiency results in a mixed phenotype of a Glycogen Storage Disorder and a Congenital Disorder of Glycosylation (CDG). Screening for abnormal glycosylation has identified more than 40 patients, manifesting with a broad clinical and biochemical spectrum which complicates diagnosis. Together with the availability of D-galactose as dietary therapy, there is an urgent need for specific glycomarkers for early diagnosis and treatment monitoring. We performed glycomics profiling by high-resolution QTOF mass spectrometry in a series of 19 PGM1-CDG patients, covering a broad range of biochemical and clinical severity. Bioinformatics and statistical analysis were used to select glycomarkers for diagnostics and define glycan-indexes for treatment monitoring. Using 3 transferrin glycobiomarkers, all PGM1-CDG patients were diagnosed with 100% specificity and sensitivity. Total plasma glycoprofiling showed an increase in high mannose glycans and fucosylation, while global galactosylation and sialylation were severely decreased. For treatment monitoring, we defined 3 glycan-indexes, reflecting normal glycosylation, a lack of complete glycans (LOCGI) and of galactose residues (LOGI). These indexes showed improved glycosylation upon D-galactose treatment with a fast and near-normalization of the galactose index (LOGI) in 6 out of 8 patients and a slower normalization of the LOCGI in all patients. Total plasma glycoprofiling showed improvement of the global high mannose glycans, fucosylation, sialylation, and galactosylation status on D-galactose treatment. Our study indicates specific glycomarkers for diagnosis of mildly and severely affected PGM1-CDG patients, and to monitor the glycan-specific effects of D-galactose therapy.